2021
DOI: 10.1186/s12936-020-03570-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of textile ‘resistance to damage’ scores with actual physical survival of long-lasting insecticidal nets in the field

Abstract: Background Attempts have been made to link procurement of long-lasting insecticidal nets (LLIN) not only to the price but also the expected performance of the product. However, to date it has not been possible to identify a specific textile characteristic that predicts physical durability in the field. The recently developed resistance to damage (RD) score could provide such a metric. This study uses pooled data from durability monitoring to explore the usefulness of the RD methodology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…ITNs with inherently high resistance to damage can be expected to last longer in the field, promoting improved survivorship, and this basic hypothesis has been confirmed by Kilian et al [ 10 ] who demonstrated that existing ITNs achieving RD scores > 50, improved survivorship in the field by approximately seven months. However, as evidenced in for example Fig.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…ITNs with inherently high resistance to damage can be expected to last longer in the field, promoting improved survivorship, and this basic hypothesis has been confirmed by Kilian et al [ 10 ] who demonstrated that existing ITNs achieving RD scores > 50, improved survivorship in the field by approximately seven months. However, as evidenced in for example Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Knowing the RD score of an ITN product before it is distributed is, therefore, a useful indicator of its inherent robustness and ability to retain physical integrity during normal use. A link between the RD performance and survivorship has been confirmed by Kilian et al who reported a correlation between RD scores and actual ITN performance in the field, where RD scores measured in the laboratory of > 50, resulted in substantially longer service life in the field [ 10 ].…”
Section: Introductionmentioning
confidence: 93%
“…The number of net users (i.e., the number of people regularly using the same net) was significantly associated with physical degradation. This correlation emphasises the need to maximise ITN coverage and physical durability [ 29 ], and reconsider current assumptions regarding target net per person rates in distribution campaigns [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical models of net survival and predictions of public-health impacts [ 7 , 24 , 36 ] can be used to improve on allocation decisions based on the standard assumed net lifetime of 3 years. There have also been efforts to better characterize the physical integrity of LLINs using resistance to damage (RD) scores [ 37 ] to predict LLIN rates of attrition and degradation under field conditions. Though not yet adopted as a tool for LLIN procurement, RD scores aim is to optimize LLIN selection as well as provide manufacturers with a framework to develop and evaluate novel products.…”
Section: Discussionmentioning
confidence: 99%